Mesophase pitch and preparation method thereof
By introducing triarylmethane structure and fluorine-containing complexes in the preparation process of mesophase asphalt, the problem of low spinning performance of existing mesophase asphalt is solved, significantly improving the mechanical properties of carbon fibers, and reducing production costs and environment Pollution risk.
Patent Information
- Application Number
- CN202411804076.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-18
AI Technical Summary
The spinning performance of existing mesophase asphalt is low, resulting in poor mechanical properties of the produced carbon fibers, and high production costs and environmental pollution risks.
The crosslinking agent benzaldehyde compound is introduced by using aromatic-rich heavy oil as raw material, and the oligomer with triarylmethane structure is synthesized through low-temperature catalytic polycondensation reaction, and the oligomer with triarylmethane structure is enriched under a strong magnetic field. Then, under negative pressure conditions, an oil-soluble fluorine-containing complex is introduced as a catalyst, and a two-stage catalytic polycondensation reaction is carried out to form a high-planar polycyclic aromatic hydrocarbon macromolecule.
It significantly improves the spinning performance of mesophase asphalt and the mechanical properties of carbon fiber, while reducing production costs and reducing environmental pollution risks.
Smart Images

Figure CN119463910A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of deep petroleum processing, and in particular to a method for preparing mesophase asphalt with excellent spinning performance and the prepared mesophase asphalt. Background Art
[0002] Mesophase asphalt is a complex mixture of polycyclic aromatic hydrocarbon molecules with different degrees of polycondensation. Under the influence of intermolecular forces, the polycyclic aromatic hydrocarbon molecules are oriented and arranged, thus showing optical anisotropy. In addition, under high temperature conditions, mesophase asphalt shows excellent plasticity and spinnability, and is a high-quality precursor material for producing high thermal conductivity, high modulus asphalt-based carbon fibers. Usually, people use aromatic-rich materials such as petroleum asphalt and coal asphalt as raw materials for synthesizing mesophase asphalt, but these raw oils have complex compositions, and aromatic molecules show different reactivity during the synthesis process, resulting in large differences in the molecular structure composition and spatial configuration of the obtained mesophase asphalt, which greatly reduces its spinning performance and the mechanical properties of the produced carbon fibers are low.
[0003] Studies have found that the structural composition characteristics of the crude oil will be "inherited" to the mesophase asphalt molecules, thereby affecting the spinning performance of the mesophase asphalt and the mechanical properties of related carbon fibers. Japan Graphite Fiber Company uses pure aromatic naphthalene as raw material and uses catalytic polycondensation reaction to prepare mesophase asphalt with excellent spinning performance. This method achieves the purpose of regulating the molecular structure composition and spatial configuration of the mesophase asphalt by controlling the composition of the crude oil, thereby improving its spinning performance. However, the pure aromatic raw materials used in this method are expensive, resulting in excessively high production costs for the mesophase asphalt. At the same time, the catalyst HF / BF3 used has high toxicity and pollution, and can cause serious personal injury and environmental pollution if not handled with care. At present, in order to reduce production costs, researchers have selected low-priced aromatic-rich heavy oil raw materials such as petroleum asphalt and coal tar, and have achieved the purpose of improving its spinning performance and the mechanical properties of carbon fibers by regulating and optimizing the synthesis process of the mesophase asphalt.
[0004] CN106147834B provides a combined method for separating catalytic cracking oil slurry and preparing mesophase asphalt, which first uses C3-C5 light hydrocarbon fractions as extraction solvents to perform supercritical or subcritical extraction on catalytic cracking oil slurry to enrich aromatic components, and then prepares mesophase asphalt through a thermal polycondensation process. This method uses a supercritical extraction process to refine the crude oil, but the thermal polycondensation reaction temperature is high, resulting in the mesophase asphalt containing more quinoline insolubles and high softening, which is not conducive to secondary processing and utilization.
[0005] CN108611113A provides a method for preparing mesophase asphalt and carbon fiber by deep oxidation-catalytic polycondensation. The method uses cycloalkyl crude oil or intermediate base crude oil as raw material, and uses air oxidation method to deeply oxidize and crosslink the raw material to obtain a modified raw material; then ZrO2 is used as a catalyst, and the modified raw material and the catalyst are mixed to prepare mesophase asphalt. Although the mesophase asphalt prepared by this method can be used to produce carbon fiber, the residual ZrO2 particles in the mesophase asphalt cannot be removed, which affects the spinning performance of the asphalt and the mechanical properties of the carbon fiber.
[0006] CN110041952A discloses a mesophase asphalt and a preparation method thereof, wherein the heavy component with a boiling point of 350-410°C in the heavy product prepared by the thermal dissolution catalytic process of lignite is used as a raw material, and the mesophase asphalt is prepared by thermal polycondensation, vacuum distillation, hydrogenation reaction, flash evaporation and thermal sensitization. The mesophase asphalt prepared by this method has a complex process route and high production cost. At the same time, the mesophase content of the obtained product is only 61wt%, which is not suitable for preparing the precursor of high-end carbon materials. Summary of the invention
[0007] In order to prepare low softening point and highly spinnable mesophase asphalt, the present invention innovatively uses aromatic-rich heavy oil as raw material, introduces a suitable cross-linking agent, synthesizes oligomers with a weak magnetic triarylmethane structure through low-temperature catalytic polycondensation reaction, and achieves enrichment and separation of oligomers with triarylmethane structure in combination with a strong magnetic field under negative pressure conditions, and then uses this as raw material, introduces an oil-soluble fluorine-containing complex as a catalyst, and uses a two-stage catalytic polycondensation reaction under negative pressure conditions to promote the further polycondensation of oligomers with triarylmethane structure to form polycyclic aromatic hydrocarbon macromolecules with high planarity. This process successfully introduces the triarylmethane structure into the mesophase asphalt molecule, which can effectively reduce the content of quinoline insolubles in the asphalt, improve the spatial configuration and stacking state of the mesophase asphalt molecules, significantly improve the asphalt spinning performance and the mechanical properties of carbon fiber, and effectively reduce the production cost of the mesophase asphalt and its carbon fiber.
[0008] One of the objects of the present invention is to provide a method for preparing mesophase pitch.
[0009] The second object of the present invention is to provide a mesophase asphalt prepared by the above method.
[0010] The third object of the present invention is to provide a carbon fiber prepared from the above-mentioned mesophase pitch.
[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0012] In a first aspect, the present invention provides a method for preparing mesophase asphalt, comprising the following steps:
[0013] (1) subjecting aromatic-rich heavy oil, a cross-linking agent benzaldehyde compound and a catalyst to a catalytic polycondensation reaction, and then subjecting the mixture to reduced pressure distillation under the action of a magnetic field to obtain an oligomer having a triarylmethane structure;
[0014] (2) subjecting the oligomer obtained in step (1) to a two-stage catalytic polycondensation reaction under the action of a catalyst to obtain an intermediate phase asphalt.
[0015] The following is a detailed description:
[0016] Step (1):
[0017] In the step (1), aromatic-rich heavy oil is used as raw material, benzaldehyde compounds are selected as cross-linking agents, and oligomers with a triarylmethane structure having weak magnetic properties are synthesized through low-temperature catalytic polycondensation reaction. Then, unreacted raw materials and catalysts are removed through reduced pressure distillation under the action of a strong magnetic field to achieve oligomer enrichment.
[0018] The aromatics-rich heavy oil in step (1) includes, but is not limited to, one or more of catalytic cracking slurry, ethylene tar, vacuum residue, and medium-temperature coal tar.
[0019] In some embodiments, the benzaldehyde compound in step (1) is one or more selected from benzaldehyde, m-methylbenzaldehyde, 2,4-dimethyl-benzaldehyde, and 3-chloro-benzaldehyde, and the amount of the benzaldehyde compound added is 0.5-2wt% of the mass of the aromatics-rich heavy oil.
[0020] Preferably, the cross-linking agent in step (1) is a mixture of benzaldehyde and m-methylbenzaldehyde, and the mass ratio of benzaldehyde to m-methylbenzaldehyde is 1:1-4:1.
[0021] In some embodiments, the catalyst in step (1) is one or more selected from sulfuric acid, nitric acid, glacial acetic acid, and p-toluenesulfonic acid, and the amount of the catalyst added is 2-6 wt % of the mass of the aromatics-rich heavy oil.
[0022] In some embodiments, the temperature of the catalytic polycondensation reaction in step (1) is 100-130° C., and the reaction time is 1-3 h;
[0023] Preferably, the temperature of the catalytic polycondensation reaction in step (1) is 110° C. and the reaction time is 1.5 h.
[0024] In the step (1), the catalytic polycondensation product is subjected to a strong magnetic field and a vacuum distillation process to achieve the enrichment of oligomers containing triarylmethane structures. The strong magnetic field strength is 1.5-3T; the vacuum distillation can be carried out in a thin film evaporator, and the vacuum distillation temperature is 210-330°C.
[0025] The weight average molecular weight distribution range of the obtained oligomer is 470-620. 13C-NMR, FT-IR and elemental analysis determined the triarylmethane carbon (C CH ) content is 10-17wt%, aromatic carbon rate (C A ) content is 50-70wt%.
[0026] Step (2):
[0027] In the step (2), an oligomer having a triarylmethane structure is used as a raw material, an oil-soluble fluorine-containing complex is introduced as a catalyst, and a catalytic polycondensation reaction is performed under negative pressure to synthesize a mesophase pitch having a high mesophase content, a low softening point and excellent spinning performance.
[0028] In some embodiments, the catalyst of step (2) is a fluorine-containing complex, preferably one or more selected from trifluoroboron pentanoate complex, perfluorooctane sulfonyl complex, hexafluorobutyl polyitaconate complex, trifluoromethylacetophenone complex, and the added amount of the catalyst is 1-3 wt% of the oligomer weight.
[0029] In some embodiments, the two-stage catalytic polycondensation reaction of step (2) is divided into two stages. The reaction temperature of the first stage is 310-350°C, the reaction pressure is -20 to -50 kPa, and the reaction time is 0.5-2 h; the reaction temperature of the second stage is 380-410°C, the reaction pressure is -70 to -100 kPa, and the reaction time is 5-15 min.
[0030] Preferably, the reaction temperature of the first stage is 335° C., the reaction pressure is -44 kPa, and the reaction time is 1 h, and the reaction temperature of the second stage is 405° C., the reaction pressure is -90 kPa, and the reaction time is 7 min.
[0031] The weight average molecular weight distribution range of the obtained mesophase asphalt is 960-1180.
[0032] In a second aspect, the present invention provides a mesophase asphalt prepared by the above method.
[0033] The mesophase asphalt obtained by the invention has a high mesophase content (greater than 98%) and a low softening point (SP≤280°C). The method introduces an appropriate amount of triarylmethane structure into the mesophase asphalt molecule, improves the molecular spatial configuration, and significantly improves the mesophase asphalt spinning performance and the mechanical properties of carbon fiber.
[0034] Technical effect:
[0035] Mesophase asphalt is a high-quality precursor for the preparation of high-end carbon materials, and its molecular structure composition directly determines the processing and utilization of mesophase asphalt and the performance of subsequent carbon materials. The present invention innovatively introduces aldehyde cross-linking agents to prepare oligomers containing triarylmethane structures, and successfully "inherits" this structure into the mesophase asphalt molecules, significantly improving the planarity of polycyclic aromatic hydrocarbon macromolecules, effectively reducing the molecular distance, and promoting more asphalt molecules to be oriented and stacked, so that the mesophase asphalt has a lower softening point and excellent spinning performance. In addition, during the melt spinning process, the mesophase asphalt molecules with a triarylmethane structure are more easily oriented inside the fiber under the influence of shear forces, which helps to eliminate microscopic defects inside the carbon fiber and improve the mechanical properties of the carbon fiber.
[0036] In addition, the present invention innovatively develops a vacuum distillation process under the action of a high magnetic field in view of the weak magnetic characteristics of oligomers, thereby achieving efficient separation of reaction products, and the separated unreacted components can be used as raw materials for secondary processing. In the two-stage negative pressure variable temperature catalytic polycondensation reaction of the present invention, the first stage of long-term low temperature and low pressure operation promotes the further polycondensation of oligomers to form polycondensation products with higher molecular weights, ensuring that more triarylmethane structures enter the mesophase asphalt molecules, and at the same time, the small molecular components generated by the reaction are promptly removed by negative pressure operation to accelerate the catalytic polycondensation reaction. The second stage of short-term high temperature and low pressure operation promotes the further increase of asphalt molecular weight by increasing temperature and reducing pressure, effectively suppressing the occurrence of excessive polycondensation. In addition, reducing the operating pressure can remove fluorine-containing complexes, effectively reducing the heteroatom content in the mesophase asphalt, and improving the quality of asphalt.
[0037] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The figure is a schematic diagram of the process flow of the method for preparing mesophase asphalt of the present invention. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0040] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0041] Test method:
[0042] Triarylmethane carbon (C CH ) and aromatic carbon ratio (CA ) content determination: The AV-500 nuclear magnetic resonance mass spectrometer produced by BRUKER, USA, was used to determine the content of crude oil or asphalt samples. 13 C-NMR spectrum. Test process: Deuterated chloroform (CDCl3) solution is selected as solvent, the test sample is fully dissolved at room temperature, TMS is used as internal standard solvent, the resonance frequency is set to SF = 500MHz, and the time (AQ) and interval (D1) are used to be 1.6s and 2s respectively. The area integration is performed according to the relative chemical shift interval of different types of hydrogen or carbon atoms in the test sample in the spectrum in order to calculate the content distribution of different types of carbon atoms.
[0043] Example 1
[0044] like Figure 1 As shown, 2 kg of ethylene tar is weighed and transported to a reactor through a pipeline pump, 10 g of benzaldehyde and 40 g of p-toluenesulfonic acid are added, and the reaction is carried out at 110° C. for 1.5 h. Then, the reaction product is transported to a scraped film evaporator with a strong magnetic field by a pipeline pump at 100 ml / min, the high intensity of the magnetic field is set to 1.6 T, and the temperature is set to 260° C. to obtain oligomers with a molecular weight of 410-570, and the oligomer yield is 50 wt%. Then, the oligomers are transported to a 1# negative pressure reactor by a pipeline pump, and 28 g of perfluorooctane sulfonyl complex (PFOS) is added. The reaction temperature of the 1# negative pressure reactor is set to 335° C., the reaction time is 1 h, and the reaction pressure is -44 kPa. Then, the reaction product is transported to a 2# negative pressure reactor by using the negative pressure self-priming function, and the reaction temperature is set to 405° C., the reaction time is 7 min, and the reaction pressure is -90 kPa, and finally an intermediate phase asphalt with a certain softening point is obtained. With this as raw material, carbon fiber precursor was prepared by melt spinning process at 348°C, and carbon fiber with certain mechanical properties was obtained after pre-oxidation at 260°C for 4h in air atmosphere and carbonization treatment at 1200°C for 1h in nitrogen atmosphere.
[0045] Tests have shown that the molecular weight of the prepared oligomers is 410-570, combined with 13 C-NMR, FT-IR and elemental analysis determined the triarylmethane carbon (C CH ) content is 7.9wt%, aromatic carbon rate (C A ) content is 57wt%, the softening point of the obtained mesophase asphalt is 297℃, the mesophase asphalt content is 91wt%, the tensile strength of the carbon fiber is 1.5GPa, and the tensile modulus is 384GPa.
[0046] Example 2
[0047] 2 kg of ethylene tar was weighed and transported to a reactor through a pipeline pump. 10 g of m-tolualdehyde and 40 g of p-toluenesulfonic acid were added and reacted at 110° C. for 1.5 h. The reaction product was then transported to an inclined thin film evaporator with a strong magnetic field at a rate of 100 ml / min using a pipeline pump. The high intensity of the magnetic field was set to 1.6 T and the temperature was set to 260° C. to obtain oligomers with a molecular weight of 390-520 and an oligomer yield of 45 wt%. The product was then transported to a No. 1 negative pressure reactor using a pipeline pump and 12.6 g of perfluorooctane sulfonyl complex was added. The reaction temperature of the No. 1 negative pressure reactor was set to 335° C., the reaction time was set to 1 h, and the reaction pressure was set to -44 kPa. The reaction product was then transported to a No. 2 negative pressure reactor using a negative pressure self-priming function. The reaction temperature was set to 405° C., the reaction time was set to 7 min, and the reaction pressure was set to -90 kPa. Finally, an intermediate phase asphalt with a certain softening point was obtained. With this as raw material, carbon fiber precursor was prepared by melt spinning process at 345°C, and carbon fiber with certain mechanical properties was obtained after pre-oxidation at 260°C for 4h in air atmosphere and carbonization treatment at 1200°C for 1h in nitrogen atmosphere.
[0048] The test found that the molecular weight of the prepared oligomer was 390-520, combined with 13 C-NMR, FT-IR and elemental analysis determined the triarylmethane carbon (C CH ) content is 8.5wt%, aromatic carbon rate (C A ) content is 61wt%, the softening point of the obtained mesophase asphalt is 291°C, the mesophase asphalt content is 89wt%, the tensile strength of the carbon fiber is 1.8GPa, and the tensile modulus is 484GPa.
[0049] Example 3
[0050] 2kg of ethylene tar was weighed and transported to a reactor through a pipeline pump. 10g of benzaldehyde and 10g of m-methylbenzaldehyde and 40g of p-methylbenzenesulfonic acid were added and reacted at 110°C for 1.5h. Then, the reaction product was transported to an inclined thin film evaporator with a strong magnetic field by a pipeline pump at 100ml / min. The high intensity of the magnetic field was set to 1.6T and the temperature was set to 260°C to obtain oligomers with a molecular weight of 470-620 and an oligomer yield of 70wt%. Then, the oligomers were transported to a No. 1 negative pressure reactor by a pipeline pump and 28g of perfluorooctane sulfonyl complex was added. The reaction temperature of the No. 1 negative pressure reactor was set to 335°C, the reaction time was 1h, and the reaction pressure was -44kPa. Then, the reaction product was transported to a No. 2 negative pressure reactor by using the negative pressure self-priming function. The reaction temperature was set to 405°C, the reaction time was 7min, and the reaction pressure was -90kPa. Finally, an intermediate phase asphalt with a certain softening point was obtained. With this as raw material, carbon fiber precursor was prepared by melt spinning process at 335°C, and carbon fiber with certain mechanical properties was obtained after pre-oxidation at 260°C for 4h in air atmosphere and carbonization treatment at 1200°C for 1h in nitrogen atmosphere.
[0051] Tests have shown that the molecular weight of the prepared oligomer is 470-620, combined with 13 C-NMR, FT-IR and elemental analysis determined the triarylmethane carbon (C CH ) content is 16.1wt%, aromatic carbon rate (C A ) content is 63wt%, the softening point of the obtained mesophase asphalt is 280°C, the mesophase asphalt content is 99wt%, the tensile strength of the carbon fiber is 3.5GPa, and the tensile modulus is 684GPa.
[0052] Comparative Example 1
[0053] Weigh 2kg of ethylene tar, transport it to a reactor through a pipeline pump, react at 110°C for 1.5h, and then use a pipeline pump to transport the reaction product to a scraped film evaporator with a strong magnetic field at 100ml / min. The high intensity of the magnetic field is set to 1.6T and the temperature is set to 260°C to obtain oligomers with a molecular weight of 340-500 (the raw oil contains a small amount of components with a molecular weight of 340-500, which can be enriched by vacuum distillation). Then, it is transported to a two-stage negative pressure reactor, wherein the reaction temperature of the 1# negative pressure reactor is set to 335°C, the reaction time is 1h, and the reaction pressure is -44kPa, and the reaction temperature of the 2# negative pressure reactor is set to 405°C, the reaction time is 7min, and the reaction pressure is -90kPa, and finally an intermediate phase asphalt with a certain softening point is obtained. With this as raw material, carbon fiber precursor was prepared by melt spinning process at 315°C, and carbon fiber with certain mechanical properties was obtained after pre-oxidation at 260°C for 4h in air atmosphere and carbonization treatment at 1200°C for 1h in nitrogen atmosphere.
[0054] Tests have shown that the molecular weight of the prepared oligomer is 340-500, combined with 13 C-NMR, FT-IR and elemental analysis determined the triarylmethane carbon (C CH ) content is 4wt%, aromatic carbon rate (C A ) content is 51wt%, the softening point of the obtained mesophase asphalt is 265℃, the mesophase asphalt content is 61wt%, the tensile strength of the carbon fiber is 0.5GPa, and the tensile modulus is 108GPa.
[0055] Comparative Example 2
[0056] Weigh 2kg of ethylene tar, transport it to a reactor through a pipeline pump, add 10g of benzaldehyde and 10g of m-methylbenzaldehyde, 40g of p-methylbenzenesulfonic acid, react at 110°C for 1.5h, then use a pipeline pump to transport the reaction product to an inclined thin film evaporator with a strong magnetic field at 100ml / min, the high intensity of the magnetic field is set to 1.6T, the temperature is set to 260°C, and a molecular weight of 470-620 oligomers is obtained, and the oligomer yield is 70wt%, then use a pipeline pump to transport it to 1# negative pressure reactor, set the reaction temperature of 1# negative pressure reactor to 335°C, the reaction time to 1h, and the reaction pressure to -44kPa, then use the negative pressure self-priming function to transport the reaction product to 2# negative pressure reactor, set the reaction temperature to 405°C, the reaction time to 7min, and the reaction pressure to -90kPa, and finally obtain an intermediate phase asphalt with a certain softening point. With this as raw material, carbon fiber precursor was prepared by melt spinning process at 325°C, and carbon fiber with certain mechanical properties was obtained after pre-oxidation at 260°C for 4h in air atmosphere and carbonization treatment at 1200°C for 1h in nitrogen atmosphere.
[0057] Tests have shown that the molecular weight of the prepared oligomer is 470-620, combined with 13 C-NMR, FT-IR and elemental analysis determined the triarylmethane carbon (C CH ) content is 16.1wt%, aromatic carbon rate (C A ) content is 63wt%, the softening point of the obtained mesophase asphalt is 277°C, the mesophase asphalt content is 82wt%, the tensile strength of the carbon fiber is 1.7GPa, and the tensile modulus is 284GPa.
[0058] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A method for preparing mesophase asphalt, characterized in that: The following steps are involved: (1) subjecting aromatic-rich heavy oil, a cross-linking agent benzaldehyde compound and a catalyst to a catalytic polycondensation reaction, and then subjecting the mixture to reduced pressure distillation under the action of a magnetic field to obtain an oligomer having a triarylmethane structure; (2) subjecting the oligomer obtained in step (1) to a two-stage catalytic polycondensation reaction under the action of a catalyst to obtain an intermediate phase asphalt.
2. The method according to claim 1, characterized in that The aromatics-rich heavy oil in step (1) is one or more selected from catalytic cracking slurry, ethylene tar, vacuum residue, and medium-temperature coal tar.
3. The method according to claim 1, characterized in that The benzaldehyde compound in step (1) is one or more selected from benzaldehyde, m-methylbenzaldehyde, 2,4-dimethyl-benzaldehyde, and 3-chloro-benzaldehyde, and the amount of the benzaldehyde compound added is 0.5-2wt% of the mass of the aromatics-rich heavy oil.
4. The method according to claim 1, characterized in that: The catalyst in step (1) is one or more selected from sulfuric acid, nitric acid, glacial acetic acid, and p-toluenesulfonic acid, and the amount of the catalyst added is 2-6wt% of the mass of the aromatics-rich heavy oil.
5. The method according to claim 1, characterized in that: The temperature of the catalytic polycondensation reaction in step (1) is 100-130° C., and the reaction time is 1-3 h; Preferably, the magnetic field strength in step (1) is 1.5-3T; and the temperature of the reduced pressure distillation is 210-330°C.
6. The method according to claim 1, characterized in that The catalyst in step (2) is a fluorine-containing complex, preferably one or more selected from ethyl boron trifluoride pentanoate complex, perfluorooctane sulfonyl complex, hexafluorobutyl polyitaconate complex, trifluoromethylacetophenone complex, and the added amount of the catalyst is 1-3wt% of the weight of the oligomer.
7. The method according to claim 1, characterized in that The two-stage catalytic polycondensation reaction of step (2) is divided into two stages. The reaction temperature of the first stage is 310-350°C, the reaction pressure is -20 to -50 kPa, and the reaction time is 0.5 to 2 h; the reaction temperature of the second stage is 380-410°C, the reaction pressure is -70 to -100 kPa, and the reaction time is 5 to 15 min.
8. A mesophase pitch, characterized in that: The method is prepared by any one of claims 1 to 7.
Citation Information
Patent Citations
A combined method for separating catalytic cracking slurry and preparing mesophase asphalt
CN106147834B
Method for preparing mesophase pitch and carbon fiber through deep oxidation-catalytic condensation
CN108611113A
Mesophase pitch and preparation method thereof
CN110041952A
Cited By
Superconductive carbon black co-production method based on directional refining of catalytic slurry oil and product of superconducting carbon black co-production method
CN121006088A